PERANCANGAN SISTEM PERPUSTAKAAN ONLINE DI MA AL HASAN DENGAN METODE SPIRAL BERBASIS WEB - Suhermanto .; Riza Apriansyah (Jurnal informasi dan komputer, 2022)
Information Technology has become the main choice in creating an information system that can provide precise and accurate information. The library system at Madrasah Aliyah (MA) Al Hasan, Ciamis Regency still uses a manual system. This system is not suitable for borrowing books and returning books still using books or paper in transactions, so it takes a long time to manage the data recording of borrowing and returning books. From the description of the problem above, a library data management system is needed at Madrasah Aliyah (MA) Al Hasan, Ciamis Regency so that the system becomes more efficient as well as the borrowing and returning system which is often problematic and takes a long time. So it requires development by utilizing existing technology, for example using a website and making it easier for officers to record borrowing and returning books. The research method used in this research is the spiral method. As a result, this library information system can make it easier for librarians to manage library data and speed up the reporting process by selecting the print option.Keywords : Spiral Model, Library, Online, System